POPULATION AND HARVEST DATA FOR MERRIAM'S TURKEYS IN NEBRASKA - Karl E. Menzel (Wildlife Society Bulletin)
Abstract Wild turkey (Meleagris gallopavo merriami) surveys in Nebraska showed little agreement in indicating populations. Fall hunting success can best be predicted by abundance of pine seed and summer hen:poult ratios.